Холодное выдавливание полости матрицы для аппаратов высокого давления в условиях действия дифференцированного противодавления - Пиманов, В. В. (НТУ "ХПИ", 2014)
Приведены результаты компьютерного моделирования методом конечных элементов холодного выдавливания полости в заготовке из стали Р6М5 в условиях действия дифференцированного противодавления на свободную поверхность заготовки. Установлено: необходимое максимальное противодавление, которое обеспечивает выдавливание без разрушения; конечные размеры изделий; усилия процесса; распределения напряжений на деформирующем инструменте; напряжённо-деформированное состояние и степень использования ресурса пластичности металла. Спроектирована и изготовлена штамповая оснастка. Проведено экспериментальное выдавливание полости матриц из стали Р6М5 для аппаратов высокого давления. Выполнен анализ микроструктуры на характерных участках деформированной заготовки

The article presents results of computer simulation by finite element method of cold forging of cavity differential backpressure in workpiece made of steel P6M5 in condition of differential backpressure on the free surface of workpiece for pressure washers. Modeling was performed using the software package DEFORM. It was found by simulation determined required backpressure that provides forging without destruction, finale detail's dimensions, forces of forging process, stress distribution on work tools (punch, master-punch and container), the stress-strain state and the degree of metal plasticity utilization in the volume of deformed workpiece. A die tooling is designed and made on the basis of obtained data. The experimental forging of die cavity made of steel P6M5 for apparatus of high pressure. Experimental study on the extrusion die cavity differential backpressure of hydraulic press PO443 force of 20 MN. The microstructure analysis on specific areas of deformed workpiece is carried out
Cold forging of die cavity for high pressure apparatuses in condition of differential backpressure
Keywords: мастер-пуансон; моделирование; метод конечных элементов; микроструктура; штамповая оснастка; cold forging; die cavity; differential backpressure; master-punch; simulation; finite element method; microstructure